2023
DOI: 10.1590/1984-0462/2023/41/2021389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mortality and survival without major morbidities of very preterm infants with very low birth weight from Japan and Brazil

Abstract: Objective: This study was carried out to understand the disparities in mortality and survival without major morbidities among very premature and very low birth weight infants between participating Neonatal Intensive Care Units (NICUs) from the Brazilian Network on Neonatal Research (RBPN) and the Neonatal Research Network of Japan (NRNJ). Methods: Secondary data analysis of surveys by the RBPN and NRNJ was performed. The surveys were conducted in 2014 and 2015 and included 187 NICUs. Primary outcome was morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…According to the findings, moderate-to-severe BPD continues to be the most common severe outcome of VPIs in Shenzhen, accounting for the majority of the morbidities. Similarly, according to the neonatal research networks of Japan and Brazil, the reported prevalence of BPD in newborns is high at 18.2% and 19.2%, respectively (17). Our finding of 90.70% antenatal corticosteroid use is the potential reasons, antenatal corticosteroid have been demonstrated to improve neonatal outcomes in preterm infants.…”
Section: Discussionsupporting
confidence: 67%
“…According to the findings, moderate-to-severe BPD continues to be the most common severe outcome of VPIs in Shenzhen, accounting for the majority of the morbidities. Similarly, according to the neonatal research networks of Japan and Brazil, the reported prevalence of BPD in newborns is high at 18.2% and 19.2%, respectively (17). Our finding of 90.70% antenatal corticosteroid use is the potential reasons, antenatal corticosteroid have been demonstrated to improve neonatal outcomes in preterm infants.…”
Section: Discussionsupporting
confidence: 67%